The Northern States and King Rama I - ผลดี, สำราญ (FOYER: The Journal of Humanities, Social Sciences, and Education, 2019)
This article aims to study the historical development and the relationship that arose between the northern states and Siam in the reign of King Rama I. Northern states have a continuous historical development, being a free state in the name the Lanna Kingdom, which has fallen under the influence of various states both Ayutthaya and Myanmar. Until the reign of Phra Bat Somdet Phra Chula Chom Klao Chao Yu Hua (King Rama V), who reformed the overall northern territorial government together in the name of the Payap County, which marks the end of the independence in the northern states. However, when considering such developments, it was found that in the reign of King Rama I was one of the most important periods of northern states with a policy to allow the northern states to fall under the absolute control by Bangkok with many methods for example Chiang Mai became dependency by the arrangement of the administration, grant a confidant and a certain degree authority in some northern states, appointing Phra Chao Kawila to become the ruler of Chiang Mai and strengthen camaraderie among the citizen of the northern states. These policies have a positive impact on Siam State in many respects, for instance, strengthen in the northern states have become an important barrier for preventing war from Burma including other benefits such as tribute, paying tribute, providing tribute and conscription.